Maternal iodine levels and associations with offspring outcomes and growth: a prospective birth cohort study of Chinese pregnant women - Huo, Liangliang; Zhao, Tingting; Wang, Jing; Zhang, Xuhui; Xu, Hong; Zhu, Bing; Jin, Xingyi; Zhu, Sujuan; Sheng, Qilin (Frontiers in Endocrinology, 2025)
BackgroundIodine deficiency during pregnancy has been associated with various adverse outcomes; however, recent data on iodine status among women in Hangzhou, China, remain limited.MethodsBetween 2019 and 2022, this birth cohort study enrolled 290 eligible pregnant women at ≤12 weeks of gestation. A standardized, self-developed questionnaire was used to survey each participant, covering demographic information, pregnancy details, dietary iodine intake, and related topics. Physical examination findings of each participant and their offspring were collected. Maternal urinary iodine concentration was measured in the first, second, and last trimesters of pregnancy. Offspring outcomes were evaluated by measuring weight and length at birth, 1 month, 6 months, and 18 months, along with the recording of incidences of spontaneous premature birth, small for gestational age (SGA), and low birth weight.ResultsHigher maternal urinary iodine concentration (UIC) during the third trimester was found to be a protective factor against spontaneous premature birth and SGA. Similarly, elevated maternal UIC in the second trimester was identified as a protective factor against spontaneous premature birth. No significant association was observed between low birth weight and maternal UIC in the first, second, and last trimesters. However, offspring born to mothers with iodine insufficiency in the last trimester exhibited lower birth weight and length, as well as reduced length during follow-up. Additionally, offspring of mothers with iodine insufficiency in the first trimester showed lower long-term weight and length.ConclusionsThese findings highlight the importance of enhanced monitoring of iodine status in pregnant women to mitigate related adverse outcomes.